“We want more”: perspectives of sarcopenic older women on the feasibility of high-intensity progressive resistance exercises and a whey-protein nutrition intervention - Vijayakumaran, Reena K.; Daly, Robin M.; Tan, Vina P. S. (Frontiers in Nutrition, 2023)
This qualitative study is nested within a 12-week pilot randomized-controlled, two-arm trial involving high-intensity progressive resistance training (PRT) or PRT with a multi-nutrient, whey-protein supplementation (PRT+WP) in sarcopenic older adults. The aim is to investigate sarcopenic participants' perception and barriers to this multi-modal intervention strategy that may accelerate 'realworld' implementation. Eighteen older adults (one man) with possible sarcopenia were invited to join the study, from which 16 women were randomized to a thrice weekly PRT (n=8) program (80% of 1repetitive maximum, six resistance band exercises) only or PRT plus daily weekday milk-based WP supplementation (PRT+WP, n=8). Muscle strength (handgrip, 5-times sit-to-stand), mass (dual energy X-ray absorptiometry) and performance (Short Physical Performance Battery, stair ascend-descend), and nutrition status (Mini Nutritional Assessment) were assessed for changes. We randomly selected eight women for the semi-structured interview. Post-intervention, eight women (50%) were sarcopenia-free, 6 (38%) remained as possible sarcopenia, one (6%) woman improved to be sarcopenia and one (6%) deteriorated from possible to severe sarcopenia. There were no significant between-group differences but significant within-group improvements (p<0.05) were detected for handgrip strength (PRT+WP 5.0 kg, d=0.93; PRT 6.1 kg, d=0.55), 5-times sit-to-stand time (PRT 2.0 s, d=1.04), nutrition score (PRT+WP 3.44, d=0.52; PRT 1.80, d=0.44) and stair ascending rate (PRT+WP 0.97 s, d=0.77; PRT 0.75 s, d=0.97). Our thematic analyses identified four main themes: 1) perceived benefits, 2) sustaining behavior changes, 3) challenges in participating, and 4) improved well-being. Participants expressed how they initially were skeptical and doubted that they could complete the exercises or tolerate the milk-based WP supplements. However, they reported positive experiences and benefits felt from strength gains, increased confidence and better physical abilities. Participants were surprised on zero adverse effects of WP supplements. The women wanted more nutritional information and structured, guided exercise programs and suggested a community-based implementation. In conclusion, our findings showed PRT was well received and may support reduced risks of sarcopenia. No added benefits were seen with addition of WP supplementation, but a larger sample is required to address this question. Overall, older (previously) sarcopenic Malay women indicated they want more multi-modal programs imbedded in their community.